Hepatic Glucose Output Inhibition by Mexican Plants Used in the Treatment of Type 2 Diabetes - Mata-Torres, Gerardo; Andrade-Cetto, Adolfo; Espinoza-Hernández, Fernanda Artemisa; Cárdenas-Vázquez, René (Frontiers in Pharmacology, 2020)
De novo hepatic glucose production or hepatic gluconeogenesis is the main contributor to hyperglycemia in the fasting state in patients with type 2 diabetes (T2D) owing to insulin resistance, which leads to at least twice as much glucose synthesis compared to healthy subjects. Therefore, control of this pathway is a promising target to avoid the chronic complications associated with elevated glucose levels. Patients with T2D in the rural communities of Mexico use medicinal plants prepared as infusions that are consumed over the day between meals, thus following this rationale (consumption of the infusions in the fasting state), one approach to understanding the possible mechanism of action of medicinal plants is to assess their capacity to inhibit hepatic glucose production. Furthermore, in several of these plants, the presence of phenolic acids able to block the enzyme glucose-6-phosphatase (G6Pase) is reported. In the present work, extracts of Ageratina petiolaris, Bromelia karatas, Equisetum myriochaetum, Rhizophora mangle, and Smilax moranensis, which are Mexican plants that have been traditionally used to treat T2D, were assayed to evaluate their possible hepatic glucose output (HGO) inhibitory activity with a pyruvate tolerance test in 18-h fasted STZ-NA Wistar rats after oral administration of the extracts. In addition, the in vitro effects of the extracts on the last HGO rate-limiting enzyme G6Pase was analyzed. Our results showed that four of these plants had an effect on hepatic glucose production in the in vivo or in vitro assays. A. petiolaris and R. mangle extracts decreased glucose output, preventing an increase in the blood glucose levels and sustaining this prevented increase after pyruvate administration. Moreover, both extracts inhibited the catalytic activity of the G6Pase complex. On the other hand, even though S. moranensis and B. karatas did not exhibit a significant in vivo effect, S. moranensis had the most potent inhibitory effect on this enzymatic system, while the E. myriochaetum extract only inhibited hepatic glucose production in the pyruvate tolerance test. Because of the traditional method in which diabetic patients use plants, hepatic glucose production inhibition seems to be a mechanism that partially explains the common hypoglycemic effect. However, further studies must be carried out to characterize other mechanisms whereby these plants can decrease HGO.